2022
DOI: 10.2147/ijwh.s387259
|View full text |Cite
|
Sign up to set email alerts
|

Dietary, Psychological and Lifestyle Factors Associated with Premenstrual Symptoms

Abstract: Purpose To measure the associations of diet, psycological distress, and lifestyle factors with premenstrual symptoms (PMSx) in women in Riyadh, Saudi Arabia. Patients and Methods An interview-based, cross-sectional study was conducted on 1831 women aged 18–50 years seen in primary healthcare centers and teaching institutes in Riyadh from December 2015 to June 2016. Question topics included sociodemographics, physical activity, smoking, and dietary habits information. PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…The current study found no significant association between daily physical exercise and PMS symptoms, which is consistent with the results of Hashim et al 26 Contrary to AlQuaiz et al who found a significant association between low physical exercise and breast pain. 29 Participants who suffered from heavy menstrual bleeding had a higher prevalence of certain reported symptoms, such as abdominal pain and headaches. This is in line with Kamat et al who reported that menorrhagia was related to PMS.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found no significant association between daily physical exercise and PMS symptoms, which is consistent with the results of Hashim et al 26 Contrary to AlQuaiz et al who found a significant association between low physical exercise and breast pain. 29 Participants who suffered from heavy menstrual bleeding had a higher prevalence of certain reported symptoms, such as abdominal pain and headaches. This is in line with Kamat et al who reported that menorrhagia was related to PMS.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the manuscript “Dietary, Psychological and Lifestyle Factors Associated with Premenstrual Symptoms” by AlQuaiz A and coworkers 1 and found it extremely important from the point of view of the impact of lifestyle on premenstrual symptoms.…”
Section: Dear Editormentioning
confidence: 99%
“…29 Yapılan başka bir araştırmada ise PMS semptomları arasında yer alan anksiyete ve duygudurum bozuklukları ve karın/bel ağrıları ile basit şeker alımı arasında pozitif ilişki saptanmıştır (sırasıyla OR: 1,53; %95 CI = 1,07-2,19, p<0,05; OR: 1,84; %95 CI = 1,17-2,88, p < 0,05). 30 Batı tarzı beslenme düzeni, akut ve kronik inflamasyonla yakından ilişkilidir. Yapılan çalışmalarda PMS'li kadınlarda inflamatuar belirteçlerin (örn.…”
Section: üNiversiteunclassified